Simulation of screw runner for cylindrical basin of gravitational water vortex power plant (GWVPP) - Bhattarai, Niroj; Chalaugain, Raj Kumar (Journal of Innovations in Engineering Education, 2022)
Gravitational water vortex plant is an emerging technology to extract energy created from vortex formation in ultra-low head range. This research was conducted to test a modification in Archimedes screw as a new type of runner for Gravitational water vortex plant, considering atmospheric opening at the topmost surface of the channel. After CFD optimization, the optimum dimension for screw runner was found to have 2 blades, 267 mm height, 180 mm radius from center axis, 160 mm pitch and is positioned 235.5 mm from the top surface of the gravitational water vortex basin. Runners with blade number two and three were found to be more efficient than single and four blade runners. Out of all runners, the efficiency and output power of the two-blade screw runner was found to be a maximum of 4.07 % and 1.004 Watts respectively at 55 rpm. Further analysis of the optimized runner was done by varying the inlet speed of the water at the canal from 0.25 m/s to 0.75 m/s and found that efficiency increased with increasing inlet speed.